The opportunities, benefits, and challenges of applying health psychology in non-academic settings: summary of a roundtable discussion - Alice Le Bonniec; Lisa Hynes; Koula Asimakopoulou; Ana-Maria Schweitzer; Alexandra Dima (European Health Psychologist, 2026)
This article summarizes a roundtable discussion about the application of health psychology in non-academic settings that was presented at the EHPS conference 2024. Five contributors shared their experiences applying health psychology in non-academic settings. Contributors’ non-academic roles reflect a variety of applications for health psychology: cancer screening; cardiovascular disease prevention, medication adherence, pharmacy, and management of chronic conditions. They discussed the benefits of their roles such as adding a deeper level of analysis of people’s behaviour, integrating a user-friendly approach, use valuable tools in multi-disciplinary initiatives, making opportunity for creativity and innovation, and supporting a patient-centered approach. Challenges were also highlighted, such as short timelines, dominance of the biomedical model, low awareness and lack of credibility of the benefits of health psychology, and difficulties in measuring the impact of health psychology interventions. In conclusion, while adopting an evidence-based approach through the use of frameworks, theories and methods from health psychology in non-academic settings is highly beneficial, it requires flexibility and adaptation.